Analysis of Macro Factors of Welfare Lottery Marketing Based on Big Data - Li, Cheng; Shao, Hua; Zhang, Tiancheng; Yu, Ge (Web Information Systems and Applications, 2019)
In order to analyze various factors of welfare lottery marketing in China objectively, we utilize several regression models to analyze the macro factors of the annual sales of welfare lottery. Afterwards, we adopt different CART decision tree models to analyze the micro factors of the daily sales of welfare lottery. The experimental results show that the learned rules can provide an objective basis for scientific selection of marketing strategies.